Implementation of Regional Regulation No. 08 of 2014 concerning Waste Management in Pekanbaru City (Case Study of Senapelan District) - Angelia, Agnes; Meiwanda, Geovani (CV. Rayyan Dwi Bharata, 2023)
Garbage has become a national problem so that its management needs to be tried in a comprehensive and integrated way from upstream to downstream so that it provides economic benefits, is healthy for residents, and is safe for the area, and can change people's attitudes. Especially in the city of Pekanbaru, we hear about garbage cases. The condition of the environment in densely populated areas, especially Senapelan District, cannot be said to be clean because there are still piles of garbage on the side of the road or on vacant land, and there are still many Temporary Waste Storage Places that do not provide suitable containers. This research is to find out the implementation of Pekanbaru City regional regulations No. 8 of 2014 concerning waste management in the Senapelan District case study. The purpose of this research is to analyze the process of implementing waste management policies in the District of Senapelan. This study uses qualitative methods with case studies in order to investigate and examine phenomena that occur in real life. The results of the study show that the implementation of the Waste Management Policy in Senapelan District has generally been carried out, but it is still not optimal, as can be seen from 1. The behavior of the organizational relationship between self-management and privatization has been tried by establishing cooperation, commitment, and coordination with the Living Area and Cleaning Service, there are still obstacles in the waste management process. 2. The behavior of the implementor below has carried out waste management but there is still a lack of organizational control in the waste management process. 3. The attitude of the target group is that residents share positive reactions and support the existence of waste management in the Senapelan District. Because it is considered very helpful for urban residents, especially in densely populated areas.